(untitled) (Archives of Clinical Psychiatry, 2004)
This article describes neurophysiological and clinical aspects of repetitive transcranial magnetic stimulation (rTMS), especially low frequency rTMS. Neuroimaging techniques and hypothesis about long term actions of rTMS are discussed. Some results of low frequency rTMS on the treatment of depression are mentioned, especially one study in the University of Brasilia using low frequency rTMS twice a week, during 4 weeks in 10 patients. In this study, using the 17 item Hamilton scale, patients were scored at three different moments: T-0, T-1 and T-2, respectively, at the beginning, at the middle and at the end of the treatment. According to x² Friedman´s test there was a significant decrease (p < 0,01) in depression scores. When the three moments were compared. Possible advantages of this technique are discussed.